INVESTIGATING PECTORAL SHAPES AND LOCOMOTIVE STRATEGIES FOR CONCEPTUAL DESIGNING BIO-INSPIRED ROBOTIC FISH - Mainong, A. I.; Ayob, A. F.; Arshad, M. R. (Engg Journals Publications, 2017)
This paper describes the performance analysis of a conceptual bio-inspired robotic fish design, which is based on the morphology similar to the boxfish (Ostracion melagris). The robotic fish prototype is driven by three micro servos; two on the pectoral fins, and one on the caudal fin. Two electronic rapid prototyping boards were employed; one for the movement of robotic fish, and one for the force sensors measurements. The robotic fish were built using fused deposition modeling (FDM), more popularly known as the 3D printing method. Several designs of pectoral fins (rectangular, triangular and quarter-ellipse) with unchanging the value of aspect ratio (AR) employed to measure the performance of the prototype robotic fish in terms of hydrodynamics, thrust and maneuvering characteristics. The analysis of the unmanned robotic system performance is made experimentally and the results show that the proposed bio-inspired robotic prototype opens up the possibility of design optimization research for future work.